Photoresponsive Polymer‐Based Biomimetic Contractile Units as Building Block for Artificial Muscles. Issue 9 (5th June 2022) - Vitale, Giulia; Grandinetti, Bruno; Querceto, Silvia; Martella, Daniele; Tesi, Chiara; Poggesi, Corrado; Cerbai, Elisabetta; Wiersma, Diederik S.; Parmeggiani, Camilla; Ferrantini, Cecilia; Sacconi, Leonardo
Abstract: Loss of muscular mechanical function occurs in several diseases affecting millions of people worldwide, including heart failure, stroke, and neuromuscular disorders. To date, no medical or surgical treatments can restore muscular contractility, and the development of artificial muscles is of extreme interest. Mimicking biological muscles, which are optimized systems displaying quick reaction times, is not trivial; only few examples are reported, mainly focused on the use of biomimetic smart materials. Among them, liquid crystalline elastomers (LCEs) can be biocompatible, show contraction parameters comparable to those of native striated muscles, and are able to effectively potentiate cardiac contraction in vitro. To go further and develop in vivo implantable devices, the integration of the stimulation system with the LCE material represents an essential step. Here, a light‐stimulated biomimetic contractile unit (BCU), combining ultra‐thin photoresponsive LCE films and mini‐LED (mLED) matrixes is described. BCU performance (in terms of extent and kinetics of contractile force and shortening) can be fine‐tuned by modulating both mLED light power and spatial stimulation patterns, allowing to reproduce mechanical dynamics of native muscles. These results pave the way for the development of novel LCE‐based contraction assist devices for cardiac, skeletal, or smooth muscle support by assembling multiple BCUs. Abstract : A biomimetic contractile unit (BCU), integrating photo‐responsive liquid crystal elastomer with mini‐LED matrixes, is developed for in situ activation. An integrated contractile unit capable to convert electrical power into mechanical work is prepared and demonstrated able to mimic the native cardiac muscle function.